Réponses

2012-09-09T22:08:09+02:00

16(x+1)²-(3x-2)²

 

développement :

16(x² + 2x + 1) - 9x² + 24x - 4

16x² + 32x + 16 - 9x² + 24x - 4

7x² + 56x +12

 

factorisation :

a² - b² = (a-b)(a+b)

 

(4x + 4 - 3x +2)(4x + 4 +3x -2)

(x +6)(7x +2)

 

résoudre f(x)=12

7x² + 56x +12 = 12

7x² + 56x = 0

7x(x +8) = 0

 

2 solutions :

x = 0 ou x = -8

 

résoudre f(x)>0

(x +6)(7x +2) > 0

 

tableau de variation :

x -6 -2/7

(x +6) - 0 + +

(7x +2)- - 0 +

f(x) = + - +

 

solution pour x définie sur ]-oo;-6[ U ]-2/7;+oo[

 

En espérant t'avoir aidé.